Do Carimbo à Mesa De Negociação: Limites Para o Controle Judicial Sobre o Acordo de Não Persecução Penal em um Sistema Acusatório - Assis, Sara Rodrigues Pereira (2024)
The expansion of spaces of consensus in Brazilian criminal justice is presented as a possibility of responding to the overload of the judicial system, its slowness and the unsatisfactory results delivered to the parties, society and the alleged perpetrator when the long path of criminal proceedings in its traditional structure ends. Since the end of the 20th century, Brazil has seen an increase in mechanisms for dealing with criminal conflicts through negotiation, with the non-prosecution agreement being the most recent instrument provided for in Brazilian legislation as an alternative to traditional criminal proceedings. Considering these changes, it is necessary to analyze the main characteristics, the possible results and the adequacy of these new mechanisms of the accusatory criminal process. In view of this, this paper sets out to examine the legal discipline conferred on the judicial control over the non-prosecution agreement, identifying the reasons for its prediction and the limits for its realization. Based on the study of specialized legal literature, legal provisions and rulings of the Brazilian Superior Courts on the matter, the aim is to verify the way in which the performance of the judging body is delimited on the manifestations of consensus in criminal proceedings and, especially, in the context of the criminal non-prosecution agreement, in order to determine to what extent the provision for this control is consistent with the procedural system of an accusatory nature, whose main characteristics will also be examined. From the study proposed herein, caution is required in interpreting the provision of judicial control over the criminal non-prosecution agreement, with a view to the Court’s effective and impartial performance in assessing the terms agreed between the defense and the prosecution. This paper also extends its analysis to forensic practice, conducting field research. From the examination of data collected through participant observation, the dynamics with which hearings aimed at the judicial approval of nonprosecution agreements have developed were studied, concluding that it is necessary to adjust the role assumed by the magistrate in controlling the non-prosecution agreements so that this control is not reduced to a mere formality, nor does it represent a usurpation of the role of the accusing body by the judge.